Rac1 is required for epithelial stem cell function during dermal and oral mucosal wound healing but not for tissue homeostasis in mice. - Rogerio M Castilho; Cristiane H Squarize; Kantima Leelahavanichkul; Yi Zheng; Thomas Bugge; J Silvio Gutkind (PLoS ONE)
Background The regenerative capacity of the skin, including the continuous replacement of exfoliated cells and healing of injuries relies on the epidermal stem cells and their immediate cell descendants. The relative contribution of the hair follicle stem cells and the interfollicular stem cells to dermal wound healing is an area of active investigation. Recent studies have revealed that the small GTPase Rac1, which regulates cell migration and nuclear gene expression, is required for hair follicle stem function but not for the normal homeostasis of the interfollicular skin. Methodology/principal findings Here we explored whether Rac1 contributes to wound healing in the skin and in the oral mucosa, the latter an anatomical site that presents similar architecture to that of the skin but is devoid of any hair follicle structures, and hence lacks hair follicle stem cells. Epidermal Rac1 gene excision led to the clearly delayed closure of cutaneous wounds. Remarkably, genetic ablation of Rac1 from the oral mucosa resulted in the complete inability of oral wounds to heal. We present evidence that the lack of oral mucosal re-epithelization may result from the reduced migratory capacity of cells lacking Rac1 together with altered expression of injury-induced proliferative and cellular stress-related expression programs. Conclusions/significance Together, these observations support that while the normal development and homeostasis of the interfollicular skin and oral mucosa do not require Rac1 function, the interfollicular and oral epithelial stem cells may require a Rac1-dependent program to orchestrate the tissue response to injury and ultimate for wound closure. Ultimately, these findings may enable the molecular characterization of the acute tissue regenerative response of these stem cell populations, thus facilitating the identification of novel molecular-targeted strategies aimed at accelerating wound closure.